and, by Attaining Oil and Gas Sovereignty by Forming Indonesia Incorporate Businesses - Yoga Partamayasa; Rafiqi Anjasmara (Fakultas Hukum Universitas Hang Tuah, 2020)
Oil and gas are non-renewable types of natural resources. On the other hand, in the current era human dependence on oil and gas is very high. To meet Indonesia's national needs for natural resources, Article 33 of the Indonesian Constitution has mandated that